Analisis Karakteristik Morfologi Famili Zingiberaceae di Desa Segara Katon, Kecamatan Gangga Kabupaten Lombok Utara - Moh. Fauzan Azima; Sofiyatur Rahmah; Firman Ali Rahman (Yayasan Tajuk Indonesia, 2024)
Zingiberaceae is a long-lived terna, the characteristic of this family is the rhizomes that have an aromatic odour, have rhizomes that enlarge like tubers and have thick roots, and usually have spaces filled with volatile oils. Zingiberaceae is better known to the public as ginger-ginger plants and has been used as a spice and traditional medicine. This study aims to inventory the Zingiberaceae family in Segara Katon Village, North Lombok Regency, NTB. The methods used in this study were observation and exploration methods with data collection techniques using simple random sampling. This type of research is descriptive qualitative. The results found as many as 3 genus namely Curcuma, Kaemfperia, and Zingiber which include Curcuma zeodaria, Curcuma longa, Curcuma xhantorhiza, Kaempferia galanga, and Zingiber officinale. Ginger-ginger plants are also able to treat several diseases such as flu, indigestion, asthma, wounds and others. Apart from being a medicine, ginger-ginger plants are also often used as a spice.